Carcinogenic and Genotoxicity of some PAHs in commonly consumed smoked fish (Parachanna obscura and Ethmalosa fimbriata) - N.O. Erhunmwunse; S.A. Ekaye (Journal of Applied Sciences and Environmental Management)
The dietary exposure of Polycyclic Aromatic Hydrocarbon (PAHs) and potential risk to human health was instigated in two different traditionally smoked species of fish (Parachanna obscura and Ethmalosa frimbriata) purchased from three markets in Benin City. Identification and quantitative analysis of PAHs components were achieved by Gas Chromatography/High Performance Liquid Chromatography. The result obtained showed that, Benzo(a)pyrene had an occurrence of 83.33% in all samples analysed. Risk assessment conducted using benzo(a)pyrene carcinogenic and mutagenic toxicity equivalent factor (TEQ & MEQ) showed slight to high risk (7.44 x10-5 -1.95 x10-3 ) and exceeded the USEPA guideline (1.0 x 10-5 ) for potential Cancer. Levels of PAHs present in smoked fish prepared using traditional method may pose elevated cancer risks if consumed at high rates over many years.